2018
DOI: 10.1074/jbc.m117.809582
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B X-interacting protein promotes the formation of the insulin gene–transcribing protein complex Pdx-1/Neurod1 in animal pancreatic β-cells

Abstract: The activation of insulin gene transcription depends on multiple nuclear proteins, including the transcription factors PDX-1 and NEUROD1, which form a transcriptional complex. We recently reported that hepatitis B X-interacting protein (HBXIP, also termed LAMTOR5) can modulate glucose metabolism reprogramming in cancer cells. However, the physiological role of HBXIP in the modulation of glucose metabolism in normal tissues is poorly understood. Here, we report that Hbxip is an essential regulator of the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…5B-5D and Fig. 6), which are known to not only control beta cell development but also maintain mature beta cell function [18,[47][48][49][76][77][78][79]. NEUROD1, which has been reported to modulate insulin expression, has been confirmed to be regulated by miR-124a (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…5B-5D and Fig. 6), which are known to not only control beta cell development but also maintain mature beta cell function [18,[47][48][49][76][77][78][79]. NEUROD1, which has been reported to modulate insulin expression, has been confirmed to be regulated by miR-124a (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…To study the function of Hbxip in normal development, we knocked out Hbxip in previous generated Hbxip floxed mice (Figure 1A) (Li et al, 2018). Heterozygous Hbxip KO ( Hbxip +/- ) mice were obtained through mating between Hbxip floxed mice and EIIa-cre mice.…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of HBXIP in normal development remains poorly understood. Only a recent work reported that due to the pivotal role of Hbxip in activating the transcription of insulin by elevating the level of Pdx-1/Neurod1 complex, pancreatic β-cell-specific Hbxip knockout (KO) mice display higher fasting blood glucose levels and impaired glucose tolerance (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…HBXIP knockout mice have impaired glucose tolerance and reduced insulin production ( 22 ). Furthermore, HBXIP is highly expressed in pancreatic islets, acting as a coactivator of pancreatic and duodenal homeobox transcription factor and forming a complex with neurogenic differentiation 1 to upregulate insulin transcription genes and promote insulin secretion ( 22 ). Furthermore, the DNA damage response is an intrinsic signaling network in cells that recognizes and repairs DNA damage ( 27 ).…”
Section: Normal Physiological Role Of Hbxipmentioning
confidence: 99%
“…The carcinogenic mechanism of HBXIP in most tumors has been established, but its role in normal cells has been less well studied. At present, the role of HBXIP in maintaining normal glucose tolerance phenotype and normal embryonic tissue development in mice has been preliminarily studied ( 22 , 23 ). Likewise, HBXIP is involved in DNA damage repair ( 21 ).…”
Section: Introductionmentioning
confidence: 99%